Hydrodynamic cavitation as a strategy to enhance the efficiency of lignocellulosic biomass pretreatment - Hilares, Ruly Teran (2017)
Hydrodynamic cavitation (HC) is a process technology with potential for application in different areas including environmental, food processing, and biofuels production. Although HC is an undesirable phenomenon for hydraulic equipment, the net energy released during this process is enough to accelerate certain chemical reactions. The application of cavitation energy to enhance the efficiency of lignocellulosic biomass pretreatment is an interesting strategy proposed for integration in biorefineries for the production of bio-based products. Moreover, the use of an HC-assisted process was demonstrated as an attractive alternative when compared to other conventional pretreatment technologies. This is not only due to high pretreatment efficiency resulting in high enzymatic digestibility of carbohydrate fraction, but also, by its high energy efficiency, simple configuration, and construction of systems, besides the possibility of using on the large scale. This paper gives an overview regarding HC technology and its potential for application on the pretreatment of lignocellulosic biomass. The parameters affecting this process and the perspectives for future developments in this area are also presented and discussed.